Global Monitoring Report 2007 (Overview) : Confronting the Challenges of Gender Equality and Fragile States - World Bank (Global Monitoring Report, 2007)
The 2007 Global Monitoring Report on the Millennium Development Goals (MDGs) assesses the contributions of developing countries, developed countries, and international financial institutions toward meeting universally agreed development commitments. Fourth in a series of annual reports leading up to 2015, this year's report reviews key developments of the past year, emerging priorities, and provides a detailed region-by-region picture of performance in the developing regions of the world, drawing on indicators for poverty, education, gender equality, health, and other goals. Subtitled "Confronting the Challenges of Gender Equality and Fragile States", this year's report highlights two key thematic areas-gender equality and empowerment of women (the third MDG) and the special problems of fragile states, where extreme poverty is increasingly concentrated. The report, which is jointly issued by the World Bank and the International Monetary Fund, argues that gender equality and the empowerment of women are central to the development agenda. This is because gender equality makes good economic sense and because it helps advance the other development goals-including education, nutrition, and reducing child mortality. Rapid progress has been made in some areas, such as achieving educational parity for girls in primary and secondary school in most countries. But in many other dimensions-including political representation and participation in nonagricultural employment-performance still falls short. Better monitoring and efforts at mainstreaming gender equality requires realistic goals, strong leadership, technical expertise, and financing